2014
DOI: 10.1016/j.ijid.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Severity and frequency of community-onset Clostridium difficile infection on an Australian tertiary referral hospital campus

Abstract: Community-onset CDI accounts for a large proportion of C. difficile infections and has a similar potential for severe disease as hospital-acquired infection. Using a history of previous antibiotic use, proton pump inhibitor use, or recent hospitalization to predict cases is unreliable. We recommend that patients with diarrhoea being investigated in emergency departments and community practice are tested for Clostridium difficile infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…Our results were generally similar to published literature, where it has been reported that those with community-onset CDI have a median age of 61 years, 52% to 61% are female, and 11% die within 30 days [3, 28]. In our cohort, the median age was 69 years, 63% were female, and 12% died within 30 days.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results were generally similar to published literature, where it has been reported that those with community-onset CDI have a median age of 61 years, 52% to 61% are female, and 11% die within 30 days [3, 28]. In our cohort, the median age was 69 years, 63% were female, and 12% died within 30 days.…”
Section: Discussionsupporting
confidence: 91%
“…We are uncertain about how many infected subjects we missed; however, Hirshon et al found that 4% of outpatients with diarrhea tested positive for CDI between 2002 and 2007 in the US [35]. Missing subjects who only visited physician offices for CDI could explain why we captured fewer individuals with community-onset CDI than previously reported (22% versus 29% to 58% of all CDI cases [3, 4]). However, this could also be due to regional variations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Patients with HCFA-CDI received more PPIs and antibiotics within 6 months prior to CDI diagnosis, which is consistent with other studies [8].…”
Section: Ca-cdi Vs Hcfa-cdisupporting
confidence: 91%
“…By contrast, Clohessy et al did not find any differences between CA-CDI and HCA-CDI in terms of severity and outcome in Australian patients 21 . Nevertheless, our study did not explore patients with CA-CDI who were treated outside of a hospital setting.…”
Section: Page 11 Of 24mentioning
confidence: 82%